Generic functional requirements for effective school parents interaction system (SPIS) - Saip, Mohamed Ali; Mohd Noor, Noorfaizalfarid; Yahaya, Jamaiah; Baharom, Fauziah; Husin, Mohd Zabidin (2010)

(untitled)
An effective interaction system in school environment is certainly vital in order to improve communication and relationship between school and its community. Apart from that, information can be shared and exchanged easily. Through use of Internet, the drawback in old style of school-parent relationship including problem with parents do not have enough time to get involve in their children life school will be solved without doubt.Although there are some existing Internet-based systems for school-parent interaction that currently available in the market, the specifications and the features of these systems are different. Thus, this paper will propose generic functional requirements of school-parent interaction system. The proposed requirements can be used as a standard requirement which beneficial for developers in constructing an effective school-parent interaction system. Thus, reduce the development time and effort.